Timely initiation of chemotherapy: a systematic literature review of six priority cancers – results and recommendations for clinical practice. Issue 1 (January 2017) - Alexander, M.; Blum, R.; Burbury, K.; Coutsouvelis, J.; Dooley, M.; Fazil, O.; Griffiths, T.; Ismail, H.; Joshi, S.; Love, N.; Opat, S.; Parente, P.; et al.
Abstract : This review evaluated the association between time‐to‐chemotherapy (TTC) and survival in six priority cancers. A systematic review of the literature was undertaken for papers indexed in the MEDLINE and Cochrane Library databases from the earliest index until April 2014. The methodology used has been published in a separate paper (Guidelines for timely initiation of chemotherapy: a proposed framework for access to medical oncology and haematology cancer clinics and chemotherapy services). The optimal timing of chemotherapy in breast cancer is unclear as available studies are of low quality, report inconsistent results and are limited to the adjuvant setting. However, increased TTC may have a negative prognostic impact, and delays beyond 4 weeks should be avoided. Studies suggest that the optimal timing for initiation of adjuvant chemotherapy for surgically resected colorectal cancer is 4–8 weeks post‐surgery. Timing of chemotherapy for metastatic colorectal cancer does not influence survival. There is a paucity of studies to guide the timing of chemotherapy for the treatment of lymphoma and myeloma; no definitive conclusions can be drawn, and clinician discretion should be applied. The optimal timing of chemotherapy in lung cancer is unclear; however, rapid tumour growth and poor disease prognosis suggest that delays should be avoided wherever possible. The optimal timing of chemotherapy in ovarian cancer is unclear as available studies are of low level, report inconsistent results and are limited to the post‐surgery setting; however, increased TTC may have a negative prognostic impact; therefore, delays beyond 4 weeks should be avoided.